Adrenaline auto-injector injuries: Practical considerations in emergency management in a tertiary hand surgery unit. Issue 10 (10th March 2023) - McCaughran, Pierre William; Ellis, Kate; Southall, Clea; Zargaran, David; Nikkhah, Dariush; Mosahebi, Afshin
Abstract : Adrenaline auto-injectors are the first line treatment for anaphylaxis in the community setting. Both anaphylaxis and auto-injector carriage are increasing in prevalence. Adrenaline auto-injector injuries are common and most often involve the hand or digits. Such injuries carry a risk of ischemic necrosis due to profound vasoconstriction, especially if there is undying vascular pathology such as Raynaud's disease. The effects can be readily reversed with local infiltration of phentolamine. A survey was circulated to 40 clinicians working in the emergency and hand surgery departments of a major urban center. Knowledge of adrenaline duration of action and its reversal (agent, dose and location in the hospital) was assessed. All clinicians working within the two departments were eligible for participation. Only 25% of clinicians surveyed were aware of the duration of action of adrenaline. Half were aware of the correct reversal agent and only 20% knew the correct dose. Only one person was aware of phentolamine's location within the hospital. There is relatively poor clinician knowledge surrounding adrenaline reversal and a lack of easily accessible information available about dosing and drug location within the hospital. Given the time dependent nature of adrenaline auto-injector injuries Emergency Departments should consider stocking phentolamine in an emergency drugs fridge within the department along with a dosing guide. This is likely to greatly reduce time from presentation to treatment and thus the chances of digital ischemia progressing to necrosis.